Effect of education based on Pender`s health promotion model on nutrition behavior of adolescent girls - Farideh Naserpoor; Fereshteh Zamani-Alavijeh; Parvin Shahri; Amal Saki Malehi (Gonabad University of Medical Sciences, 2018)
Poor eating habits are formed and stabilized from childhood and adolescence, so, if there is no intervention to correct it, the dietary habits can be the source of health problems in the future. This study aimed to evaluate the effect of education based on Pender`s health promotion model on nutritional behavior of high school girls. This study was performed on 128 adolescents (two groups of 64 students). The data collection tool was a questionnaire designed based on the Pender`s health promotion model. Educational intervention consisted of four 45 to 60 minute training session for students and a training session for mothers with teaching methods of lecture, questioning and answering and group discussion. The two groups before the intervention were not significantly different in terms of demographic variables and the mean score of behavior and model constructs. But after the intervention, the mean score of healthy nutrition behaviors increased from 14.12 to 15.29 in the experimental group. The mean score of some model structures such as self-efficacy, perceived benefits and interpersonal norms in the test group significantly increased and the mean score of perceived barriers decreased significantly. But modeling structure didn't show significant changes. The results of this study focuses on the effectiveness of health promotion model in changing nutrition behaviors. An increase in the perceived benefits and self-efficacy as well as a reduction in the perceived barriers to healthy eating are the strategies that can be the basis of the programs that are designed to promote healthy behaviors in adolescents especially in the school environment.